Sustainable Landscape Construction: Materials and Products — Paints and Stains - Gail Hansen (EDIS)
ENH1144, a 1-page fact sheet by Gail Hansen, lists several finishes for exterior applications, with strategies for selection and use. Includes references. Published by the UF Department of Environmental Horticulture, October 2009.